Analysis of the Effectiveness of Subsidized Fertilizer Program Distribution in Indonesia - Fatika, Yeka Hendra; Umar, Haryono; Nirmalawati, Dyah (Universitas Mercu Buana, 2025)
Fertilizer subsidies represent a strategic policy instrument in Indonesia’s agricultural development agenda. Despite their significance, the implementation of subsidized fertilizer programs continues to face numerous challenges, including inaccurate targeting, weak distribution accountability, and data inconsistencies. This study aims to evaluate the effectiveness of the subsidized fertilizer program based on the